The Effect of an Educational Program Based on Self-Learning to Develop Digital Skills among Al-Aqsa University Students - Abu Mutlaq, Hana Khalil; Ibrahim, Omer Ahmed (Journal of Educational and Psychological Sciences, 2023)
The aim of the study was to identify the effect of an educational program based on self-learning on the development of digital skills among Al-Aqsa University students. The study adopted a quasi-experimental design with a single-group pretest-posttest design. The study population consisted of female students from the Department of Educational Sciences (major child education) for the academic year 2022/2023. The study sample comprised (54) students who were purposively selected. The study tools included a digital skills test. The results of the study showed statistically significant differences at a significant level (α≤0.05) between the mean scores of the students in both the pretest and posttest of the digital skills test as a whole, and its individual domains, in favor of the posttest. The results also indicated a significant impact of the self-directed learning program on the development of digital skills among the study sample. The researchers recommended the need to develop curricula that allow for the integration of digital skills within the curriculum in an integrated manner, as well as the development of training programs for instructors and university students on digital skills through interactive education programs, active participation in online courses, workshops, seminars, and conferences, and encouraging them to actively use digital technologies in teaching and learning.